ZIF-8 derived ZnWO4 nanocrystals: Calcination temperature induced evolution of composition and microstructures, and their electrochemical performances as anode for lithium-ion batteries. (20th January 2021) - He, Yuanchuan; Zhong, Linping; Wang, Xuejia; He, Jiaxin; Wang, Li; Zhong, Cheng; Liu, Mengjiao; Zhao, Yan; Lai, Xin; Bi, Jian; Gao, Daojiang
Highlights: ZnWO4 nanocrystals derived from ZIF-8 have been constructed via a facile strategy. The calcination temperature has determined crystallinity, composition and microstructure. The probable evolution mechanisms for the microstructure and the composition are proposed. The obtained sample ZWO-800 exhibits superior capacity and cyclic stability. Abstract: Calcination temperature plays a key role in determining the phase purity, composition and microstructures for the zeolitic imidazolate frameworks (ZIFs) derived transition metal oxides materials, the investigation on the influences of the calcination temperature during ZIFs derivative process is helpful to dissect the reaction mechanism and the transformation process. The present work is aimed at constructing ZnWO4 nanocrystals derived from ZIF-8 via a facile strategy, and systematical study on the influences of calcination temperature during ZIFs derivative process on the microstructure, phase purity and composition of the final product. More importantly, the probable evolution mechanisms for the microstructure and the composition of the as-obtained final products are proposed. It is found that the crystallinity, composition, microstructure and electrochemical performances of the ZnWO4 samples strongly depend on the calcination temperature. When the calcination temperature is lower than 700 °C (500 and 600 °C), the ZnWO4 /C composite nanocrystals can be obtained. Whereas the as-synthesized products are pure ZnWO4 nanocrystals featuring single crystalline under the higher calcination temperatures (700–900 °C). Due to the single crystalline structure and the optimal microstructures, the ZnWO4 sample obtained at 800 °C exhibits the superior electrochemical performances when applied as anode material for lithium-ion batteries such as excellent cyclic stability, higher capacity and better rate capability. The present work may provide the deep insight into the Zn-based materials derived from the ZIF-8, and paves a facile and general strategy for the precise control the microstructures and composition of the other transition metal oxides derived from ZIFs. Graphical abstract: Image, graphical abstract